Pengaruh Ekaristi pada Kehidupan Umat: Penelitian di Keuskupan Agung Palembang dan Keuskupan Agung Makassar - Subali, Yohanes; Anugraha, Blasius Dinda; Rupang, Gregorius (Forum, 2024)
The church considers that the Eucharist and the daily life of Christians are an inseparable unity. Active participation in the Eucharist is not limited only to liturgical rituals alone but should also be reflected in the daily lives of Christians. In this study, the author aims to examine the significance of the Eucharist as lived by the faithful in receiving the body of Christ in everyday life. This study was conducted using quantitative methods to answer the research question: Does receiving the body of Christ help the faithful realize their faith in everyday life? Various questions were posed to respondents via Google Form. The results showed that in the Archdiocese of Palembang and the Archdiocese of Makassar, receiving the body of Christ has a significant impact on daily life. This sacrament fosters a sense of solidarity and togetherness among the faithful and even encourages active participation in social activities and community service. Thus, it is hoped that the results of this study will inspire the faithful in other dioceses to better appreciate the meaning of the Eucharist in everyday life.